IoT things description method and things identification - Bowen PAN; Chao MA (物联网学报)
Starting from the current situation of IoT identification systems,the new development thoughts of IoT was discussed,and the concept of IoT things description from a different perspective was raised.IoT open system architecture was introduced,and the things description layer of the architecture was mainly explained.The things description metadata two-layer structure and the contents and meanings of every segment in the metadata structure were illustrated.Things description file was introduced and the relationship between files and identifications was explained.The role of IoT things description in the development of artificial intelligence was discussed.Then,the progress and problems of standardization of IoT things description technology were talked about.